Effect of Ionic Strength on Porphyrin Drugs Interaction with Quadruplex DNA Formed by the Promoter Region of C-myc and Bcl2 Oncogenes - Nagesh, Narayana; Sharma, Varun K.; Ganesh Kumar, A.; Lewis, Edwin A. (Journal of Nucleic Acids, 2010)
C-myc and Bcl2 are well characterized oncogenes that are capable of forming G-quadruplex structures. Promoter regions of C-myc and Bcl2 forming G-quadruplex structures are chemically synthesized and G-quadruplex structure is formed in presence of 100 mM potassium ion. Three different porphyrin drugs, namely TMPyP2, TMPyP3, and TMPyP4 are allowed to interact with quadruplex DNA complex and the site and nature of interaction are studied. Drug interactions with quadruplex DNA were carried out in different potassium ionic strengths using fluorescence spectroscopy. It is found that fluorescence hypochromicity decreases with an increase in ionic strength in the case of TMPyP4, TMPyP3, and TMPyP2. Fluorescence titration studies and Job plots indicate that four molecules of TMPyP4, two molecules of TMPyP3 and TMPyP2 are interacting with one molecule of quadruplex DNA.